Провiднiсть графену на сегнетоелектрику PVDF-TrFE - Kurchak, A. I.; Strikha, M. V. (Publishing house "Academperiodika", 2018)
The theory of conductivity in graphene grown by the chemical vapor deposition on a poly[(vinylidenefluoride-co-trifluoroethylene] (PVDF-TrFE) ferroelectric film has been developed with regard for the charge carrier scattering at large-scale potential nonuniformities created by both the domain structure of the ferroelectric and a nonuniform distribution of chemical dopants over the graphene surface. As the correlation length of nonuniformities increases, the graphene resistivity has been shown to decrease, and, in the case of a sufficiently uniform distribution of chemical dopants and the sufficiently large domain sizes, to achieve values of 100 Ω and less. Such values make the “graphene on PVDF-TrFE” system competitive with standard conductive and transparent indium tin oxide coverings for photovoltaics. The theoretical results have been compared with experimental data.